1983
DOI: 10.1071/ph830417b
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of Main-line OH Masers in the Galactic Longitude Range 3° to 60°

Abstract: Aust. J. Phys., 1983,36,417-42 We tabulate all 55 OH main-line masers discovered to date in the galactic plane between longitude 3° and 60°. For most of these we show current spectra, which have been taken with the Parkes 64 m radio telescope, in both senses of circular polarization on the 1665 MHz and/or 1667 MHz transitions; for some sources we give new position estimates, and several sources are reported for the first time. We discuss many sources individually and note that while most of the main-line OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
46
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 3 publications
9
46
0
Order By: Relevance
“…OH masers were reported in the main 1.665 and 1.667 GHz, and the satellite 1.720 GHz lines (Caswell & Haynes 1983;Edris et al 2007), whereas the 1.612 GHz OH satellite was observed in absorption. CH 3 OH thermal lines were observed at 25, 96.7, 157, 241.7, and 255 GHz by Leurini et al (2007), and maser emission was reported for the Class II 6.7 GHz (Menten 1991;Caswell et al 1995b;Szymczak et al 2000) and 12.2 GHz (Caswell et al 1995a), and the Class I 44.1 GHz (Slysh et al 1994) and95.2 GHz (Val'tts et al 2000) transitions.…”
Section: The Hmsfr G1659-005mentioning
confidence: 99%
“…OH masers were reported in the main 1.665 and 1.667 GHz, and the satellite 1.720 GHz lines (Caswell & Haynes 1983;Edris et al 2007), whereas the 1.612 GHz OH satellite was observed in absorption. CH 3 OH thermal lines were observed at 25, 96.7, 157, 241.7, and 255 GHz by Leurini et al (2007), and maser emission was reported for the Class II 6.7 GHz (Menten 1991;Caswell et al 1995b;Szymczak et al 2000) and 12.2 GHz (Caswell et al 1995a), and the Class I 44.1 GHz (Slysh et al 1994) and95.2 GHz (Val'tts et al 2000) transitions.…”
Section: The Hmsfr G1659-005mentioning
confidence: 99%
“…OH masers (e.g., Caswell & Haynes 1983;Szymczak & Gérard 2004). Through Zeeman splitting of the 1.667 GHz maser components, Szymczak & Gérard (2004) estimated a magnetic field strength of a few tenths of mG. Interestingly, in the spectra of the 1.665, 1.667, and 1.720 GHz OH transitions, absorption features were also noted (Caswell & Haynes 1983;Szymczak & Gérard 2004).…”
Section: The Hmsfr G2301-041mentioning
confidence: 99%
“…Through Zeeman splitting of the 1.667 GHz maser components, Szymczak & Gérard (2004) estimated a magnetic field strength of a few tenths of mG. Interestingly, in the spectra of the 1.665, 1.667, and 1.720 GHz OH transitions, absorption features were also noted (Caswell & Haynes 1983;Szymczak & Gérard 2004). A similar absorption pattern was observed in the 4.8 GHz H 2 CO transition by Downes et al (1980), who associated G23.01−0.41 to a nearby diffuse H ii region, identified through the H110α recombination line emission.…”
Section: The Hmsfr G2301-041mentioning
confidence: 99%
“…Introduction Caswell and Haynes (1983, present issue p. 419) recently made a compilation of all known OH masers that emit predominantly on the main-line transitions (1665 or 1667 MHz) of the ground state and are located in the galactic plane between longitude 3° and 60°. In April 1982 we conducted a search for associated H20 maser emission in the direction of those OH sources which are either new or now have greatly improved position estimates (Caswell and Haynes 1983). We used the Parkes 64 m radio telescope equipped with a new 22 GHz maser receiver and a 1024-channel correlator.…”
mentioning
confidence: 99%